Fabrication and characterization of organic - inorganic hybrid broadband photodetectors - Upadhyay, Deep Chandra (IIT (BHU), Varanasi, 2022)
In general, most of the reported organic photodetectors use two terminal device structures similar to the photovoltaic devices. Such devices mainly consist of an active layer sandwiched between the anode and cathode. In this type of photodetector structure, either the cathode or anode electrode is made to be transparent to the incident light so that light can be entered into the active layer of the device through it. In particular, the active layer in an organic photodetector may either be an organic semiconducting material or an inorganic - organic hybrid nanocomposite material. From the structural point of view, organic photodetectors are mainly classified into three types phototransistors-based OPDs (PTOPDs), photoconductors-based OPDs (PC-OPDs), and photodiodes-based OPDs (PDOPDs). The present thesis deals with the fabrication and characterization of some PM effect-based organic-inorganic hybrid broadband photodetectors. The present thesis aims to the performance optimization of such inorganic-organic photoactive material based broadband photodetectors through device structural engineering and active material engineering. A relatively less explored PTB7 polymer for the broadband photodetector applications. This thesis includes five chapters. The layout of the present thesis is briefly described in the following: Chapter 1 includes a brief introduction about the basics of organic photodetectors and the used strategies for the developing high-performance photodetectors. Some important performance parameters of the photodetectors are also discussed. A detailed literature survey on various inorganic-organic photodetectors is then presented. Various strategies used for the performance optimization of the organic-inorganic broadband photodetectors are also reviewed. Emphasis has been given primarily on the binary and ternary blend of organic-organic and organic-inorganic based photodetectors. Based on the observations from the literature survey, the scopes of the present thesis are finally defined. Chapter 2 presents a novel technique for enhancing the responsivity and EQE of a FTOcoated glass/ZnO nanorods arrays (NRAs)/PCDTBT:PCBM:PbS QDs/Ag structure based broadband photodetector. The ZnO NRAs layer acts as the electron transport layer (ETL), the hybrid organic-inorganic nanocomposite layer of the PCDTBT: PCBM: PbS QDs acts as the active layer and the MoOx layer acts as the hole transport layer (HTL) in the photodetector. The combined effects of the ETL engineering, ternary nanocomposite based active material engineering and vertical structure engineering enabled the proposed device to achieve high responsivities of ~ 213.77 A/W at 380 nm (UV), ~28.57 A/W at 550 nm (Visible), and ~7.22 A/W at 860 nm (NIR). The proposed photodetector showed a high external quantum efficiency (EQE) of greater than 1000 % at a low reverse bias of -1.5V. Chapter 3 explores the ternary inorganic-organic nanocomposite of PCDTBT: PCBM: CdSe tetrapod shaped nanocrystals (NCs) for broadband photodetector applications. A device structure of FTO/ZnO NRs/PCDTBT:PCBM:CdSe NCs/MoOx/Ag is fabricated on the FTO-coated glass substrate. The CdSe tetrapod shaped NCs are used fabricate high performance photodetectors over the commonly used spherical shaped inorganic NCs. Under a reverse bias voltage of -2 V, the proposed photodetector showed excellent photoresponse characteristics with a responsivity of 1.830 A/W (0.344 A/W), detectivity of 1.75x1012 (3.3x1011) Jones, a rise time of 5.73 s (0.02 s) and fall time of 6.41s (0.14 s) at UV-375 nm (Visible-540 nm) under a low intensity of indent light of 13.1 μWcm-2 (41.2 μWcm-2). Chapter 4 presents a simple low-cost approach to fabricate a p-PTB7/n-ZnO NRs heterojunction based high performance wideband photodetector. The performance of an FTO/ZnO NRs/PTB7/MoOx/Ag structure is investigated in this chapter. The basic objective of this study was to replace the ternary organic-inorganic nanocomposites (considered in previous chapters) by the single high-quality PTB7 ploymer to reduce both the fabrication complexity and cost of the broadband photodetectors. Under a relatively low reverse bias voltage of -1 V, the proposed device showed a high responsivities of ~ 307.18 A/W and ~ 33.64 A/W at 380 nm (UV) and 640 nm (Visible) wavelengths, respectively. The proposed device also showed the detectivities of ~ 1.56 × 1013 Jones and ~ 1.7 × 1012 Jones with the EQEs values of ~ 100230 % and ~ 6510 % at 380 nm and 640 nm wavelengths under a low −1 V bias, respectively. Finally, Chapter 5 is devoted to summarize the major findings of the present thesis. Some future scopes of works related to this thesis are also briefly outlined.
Acc. No. 1062
Keywords: Fabrication; Photodetectors; Organic-Inorganic hybrid broadband